Constraining the 21 cm brightness temperature of the IGM at z = 6.6 around LAEs with the murchison widefield array. Issue 1 (3rd August 2021) - Trott, C M; Jordan, C H; Line, J L B; Lynch, C R; Yoshiura, S; McKinley, B; Dayal, P; Pindor, B; Hutter, A; Takahashi, K; Wayth, R B; Barry, N; et al.
ABSTRACT: The locations of Ly α-emitting galaxies (LAEs) at the end of the Epoch of Reionization (EoR) are expected to correlate with regions of ionized hydrogen, traced by the redshifted 21 cm hyperfine line. Mapping the neutral hydrogen around regions with detected and localized LAEs offers an avenue to constrain the brightness temperature of the Universe within the EoR by providing an expectation for the spatial distribution of the gas, thereby providing prior information unavailable to power spectrum measurements. We use a test set of 12 h of observations from the Murchison Widefield Array (MWA) in extended array configuration, to constrain the neutral hydrogen signature of 58 LAEs, detected with the Subaru Hypersuprime Cam in the Silverrush survey, centred on z = 6.58. We assume that detectable emitters reside in the centre of ionized H ii bubbles during the end of reionization, and predict the redshifted neutral hydrogen signal corresponding to the remaining neutral regions using a set of different ionized bubble radii. A pre-whitening matched filter detector is introduced to assess detectability. We demonstrate the ability to detect, or place limits upon, the amplitude of brightness temperature fluctuations, and the characteristic H ii bubble size. With our limited data, we constrain the brightness temperature of neutral hydrogen to ΔTB <30 mK (<200 mK) at 95 per cent (99 per cent) confidence for lognormally distributed bubbles of radii, R B = 15 ± 2 h −1 cMpc.